Bioactivity of genistein: A review of in vitro and in vivo studies - Ganai, Ajaz Ahmad; Farooqi, Humaira (Biomedicine & pharmacotherapy, 2015)
Genistein is a soy derived isoflavanoid compound with multitude of health benefits. This compound is found to be a potent agent in both prophylaxis and treatment of cancer and various other chronic diseases. Ranging from its antioxidant activity to its effect on various cancer types, genistein has been a compound of interest in a number of studies carried out so far. The great interest that has focused on genistein led to the identification of numerous intracellular targets of its action in the live cells. Retardation of atherogenic activity and increasing the antioxidant defense of a cell has been attributed to genistein while as it has also been reported that genistein possesses suppressive effects on both the cell-mediated and humoral components of the adaptive immune system. At the molecular level, genistein reduces the number of developing CD4+ and CD8+ thymocytes suggesting a possible mechanism for genistein effects on cell-mediated immunity. Genistein may inhibit cancer progression by inducing apoptosis or inhibiting proliferation. In addition, genistein has its prominent role in preventing the DNA damage. Apolipoprotein B secretion gets reduced when the subjects are administered with genistein. Genistein confers a better protection to ischemic conditions thereby giving a significant cardioprotection. At cellular level adipocyte differentiation is another property of genistein which makes it a better neutraceutical which can reduce the atherogenic condition and hypercholesterolemia. Expression of human endothelial nitric oxide synthase is associated with genistein supplementation. The advantage of using genistein is its multidirectional action and its lesser toxicity.